AB1104 GENETIC ASPECTS OF SARCOIDOSIS IN A TUNISIAN POPULATION. (June 2019) - sayhi, sameh; Dhahri, Rim; Boussetta, Najah; Hannachi, Souha; Laajili, Feida; Louzir, Bassem; Derbali, Hajer; Mrisa, Linda; Mrisa, Ridha
Abstract : Background: Objectives: To determine the frequencies of the HLA alleles and genotypes of the ACE gene. Methods: This is a cross sectional study of 65 patients with sarcoidosis, followed in the departments of internal medicine and neurology at the Military Hospital of Tunis.The genetic study involved only 50 patients. DNA extraction was performed to determine the frequencies of the HLA alleles and genotypes of the ACE gene. Results: 1. HLA typing The analysis of HLA typing allowed us to estimate the different frequencies of alleles in patients. The calculation of the allelic frequency found that the most frequent alleles are HLA-DRB1 * 1501 alleles with a frequency of 38% and HLA-DRB1 * 0301 of 28%. Other alleles are at lower frequencies (Table1 ). 2. Genotyping of the ECA gene Genotyping of the polymorphism of the angiotensin converting enzyme (ACE) involved 50 patients. Genotypic frequencies (II, ID and DD) and allele frequencies (I and D) were estimated in order to evaluate the frequencies of each genotype and the 2 alleles for this pathology. The genotypic and allelic frequency results were summarized in Table 2 . Conclusion: The most frequent alleles in Tunisian patients with sarcoidosis are HLA-DRB1 * 1501 alleles with a frequency of 38% and HLA-DRB1 * 0301 of 28%. The genotypic and allelic results showed that genotype ID was the most frequent with 48% with a predominance of the D allele in 54%. References: Disclosure of Interests: None declared